2020
DOI: 10.1002/bit.27264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enzymatic reduction on bivalent bispecific antibody fragmentation and loss of product purity upon reoxidation

Abstract: Antibody disulfide bond (DSB) reduction during manufacturing processes is a widely observed phenomenon attributed to host cell reductases present in harvest cell culture fluid. Enzyme‐induced antibody reduction leads to product fragments and aggregates that increase the impurity burden on the purification process. The impact of reduction on bivalent bispecific antibodies (BisAbs), which are increasingly entering the clinic, has yet to be investigated. We focused on the reduction and reoxidation properties of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Unfortunately, BisAb development and production is often challenged by manufacturing problems due to low production yields 2 . Specifically, a common challenge observed during the production of BisAbs is high product aggregates (exceeding 40% in some cases) due to mis-pairing of engineered disulfide bonds 3 5 . Product aggregates can trigger immunogenic responses in patients and therefore must be removed, severely decreasing product yields and increasing commercial manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, BisAb development and production is often challenged by manufacturing problems due to low production yields 2 . Specifically, a common challenge observed during the production of BisAbs is high product aggregates (exceeding 40% in some cases) due to mis-pairing of engineered disulfide bonds 3 5 . Product aggregates can trigger immunogenic responses in patients and therefore must be removed, severely decreasing product yields and increasing commercial manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the desired intramolecular disulfide bonds are formed during protein expression, reductases found in the harvest cell culture media may promote scrambling by reducing properly formed disulfide bonds [ 139 , 140 , 141 , 142 ]. The reduced disulfides can then become mispaired by reoxidation in downstream manufacturing processes [ 143 ]. Fortunately, it has recently been demonstrated that high-resolution size exclusion chromatography can, in fact, be used to monitor the levels of undesired species during production [ 138 ], which is significant considering the relative similarity of the cysteine or glutathione modified variants to the parental antibodies.…”
Section: Physical and Chemical Stabilitymentioning
confidence: 99%
“…Though multi-specific antibodies (BsAbs and TsAbs) have not been as widely manufactured as monoclonal antibodies, there is a growing interest in multi-specific antibody purification in the biopharmaceutical industry in recent years (Brinkmann & Kontermann, 2017;Y. Li, 2019;Swope et al, 2020;Tustian et al, 2016;. Taking BsAb as examples, during bispecific antibody purification process, the inter-chain disulfide bond between the heavy chains in two parental mAbs need to be reduced first to generate half-mers and followed by free thiol oxidization to form bispecific antibodies.…”
Section: Disulfide Bond Reduction During Multi-specific Antibody Purificationmentioning
confidence: 99%
“…Ideally, the disulfide bonds of antibody should pair correctly before mAbs are secreted extracellularly. Correct disulfide bonds pairings are critical during the mAb development process: (1) to meet ICH Q6B specifications for biotechnological and biological products that the number and the position of disulfide bridges should be determined based on the gene sequence for the desired product (Lakbub, Shipman, & Desaire, 2018); (2) to ensure antibody drug therapy efficiency and eliminate the immunogenicity (Kao et al, 2010;Swope et al, 2020). It is also critically important for bi-and tri-specific antibody (BsAb and TsAb) stability improvement during the drug product development (Caravella & Lugovskoy, 2010;Rossi et al, 2006;Vaks, 2018).…”
Section: Introductionmentioning
confidence: 99%